Hydrogen Sulfide Inhibits the Development of Atherosclerosis with Suppressing CX3CR1 and CX3CL1 Expression - Zhang, Huili (Public Library of Science, 2012)
Hydrogen sulfide, as a novel gaseous mediator, has been suggested to play a key role in atherogenesis. However, the precise mechanisms by which H(2)S affects atherosclerosis remain unclear. Therefore, the present study aimed to investigate the potential role of H(2)S in atherosclerosis and the underlying mechanism with respect to chemokines (CCL2, CCL5 and CX3CL1) and chemokine receptors (CCR2, CCR5, and CX3CR1) in macrophages. Mouse macrophage cell line RAW 264.7 or mouse peritoneal macrophages were pre-incubated with saline or NaHS (50 µM, 100 µM, 200 µM), an H(2)S donor, and then stimulated with interferon-γ (IFN-γ) or lipopolysaccharide (LPS). It was found that NaHS dose-dependently inhibited IFN-γ or LPS-induced CX3CR1 and CX3CL1 expression, as well as CX3CR1-mediated chemotaxis in macrophages. Overexpression of cystathionine γ-lyase (CSE), an enzyme that catalyzes H(2)S biosynthesis resulted in a significant reduction in CX3CR1 and CX3CL1 expression as well as CX3CR1-mediated chemotaxis in stimulated macrophages. The inhibitory effect of H(2)S on CX3CR1 and CX3CL1 expression was mediated by modulation of proliferators-activated receptor-γ (PPAR-γ) and NF-κB pathway. Furthermore, male apoE(−/−) mice were fed a high-fat diet and then randomly given NaHS (1 mg/kg, i.p., daily) or DL-propargylglycine (PAG, 10 mg/kg, i.p., daily). NaHS significantly inhibited aortic CX3CR1 and CX3CL1 expression and impeded aortic plaque development. NaHS had a better anti-atherogenic benefit when it was applied at the early stage of atherosclerosis. However, inhibition of H(2)S formation by PAG increased aortic CX3CR1 and CX3CL1 expression and exacerbated the extent of atherosclerosis. In addition, H(2)S had minimal effect on the expression of CCL2, CCL5, CCR2 and CCR5 in vitro and in vivo. In conclusion, these data indicate that H(2)S hampers the progression of atherosclerosis in fat-fed apoE(−/−) mice and downregulates CX3CR1 and CX3CL1 expression on macrophages and in lesion plaques.